Antibacterial and anti-inflammatory bio-based carbon dot-photo-crosslinking in-situ adhesion hydrogel as well as preparation method and application thereof
By combining the bio-based carbon dots prepared by curcumin and carboxymethyl chitosan with collagen and hyaluronic acid, and preparing hydrogels through ultraviolet cross-linking reaction, the problems of repeated infection and persistent inflammation in bacterial keratitis were solved, effective antibacterial and anti-inflammatory effects were achieved, and corneal healing was promoted.
Patent Information
- Application Number
- CN202411923438.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The prior art is difficult to effectively solve the problems of repeated infections and persistent inflammation in bacterial keratitis, and traditional antibiotic treatment may lead to the development of antibacterial resistance.
The bio-based carbon dots prepared from curcumin and carboxymethyl chitosan were mixed with double-bonded collagen and functionalized hyaluronic acid to prepare antibacterial and anti-inflammatory bio-based carbon dot-photocroslinked in situ adhered hydrogels through chemical crosslinking reactions triggered by ultraviolet light.
This hydrogel not only has powerful antibacterial and anti-inflammatory properties, but also can effectively regulate the extracellular matrix, promote corneal healing, reduce the cytotoxicity to the cornea, and provide a safe and environmentally friendly treatment plan.
Smart Images

Figure CN119700649A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinking in-situ adhesion hydrogel and a preparation method and application thereof. Background Art
[0002] Bacterial keratitis (BK) is a vision-threatening ocular disease and a leading cause of corneal blindness in developing countries due to rapid bacterial invasion leading to corneal scarring. Notably, the microenvironment of BK is characterized by an imbalance between pro-inflammatory cytokines, matrix metalloproteinases (MMPs), and reactive oxygen species (ROS), which lead to extracellular matrix (ECM) degradation and inhibit the healing process. Conventional treatments, including antibiotics and corticosteroids, not only fail to address the underlying inflammatory cascade leading to recurrent infections and persistent inflammation, but can also lead to the emergence of antibiotic-resistant strains, further complicating infection management.
[0003] In recent years, zero-dimensional carbon dots (CDs) have been extensively studied and have shown good potential for application in antibacterial applications. Compared with the generation of ROS to kill bacteria, the inhibition mechanism of physical or mechanical damage may be more conducive to reducing the cytotoxicity of CDs. Depending on the surface charge, the regulatory ability of CDs on bacteria and cells is also completely different. Positively charged CDs are more likely to adhere to and penetrate bacterial cell membranes than negatively charged CDs, thereby destroying the integrity of bacterial cells. On the other hand, the fascinating thing about CDs is that the functions of CDs can be customized to exhibit a wide range of activities by selecting precursors to prepare specific CDs with precursor functions. Many studies have shown that CDs exhibit catalytic activities such as SOD, CAT, and GPx-like enzyme activities due to their size effect and abundant active sites. These nanozyme activities are used to eliminate ROS, thereby achieving cytoprotective, anti-inflammatory, or anti-tumor effects. Therefore, the inventors raised a question: Can the antibacterial and cellular redox balance of CDs be achieved by the coexistence of positive charge and nanozyme activity? However, current research has paid less attention to how to design the balance of multiple properties of CDs to achieve different regulatory abilities on bacteria and cells, and there are almost no reports on their use in the development of corneal substitutes.
[0004] Injectable adhesive hydrogels have been shown to be effective in suturing various wounds, including ocular wounds, and thus have become an attractive alternative to sutures. The fluid precursor of the hydrogel is injected into the target site and cross-linked to adapt to irregular wounds or shapes, thereby better integrating with native tissue. Therefore, the combination of sutureless hydrogels with nanozyme-active antimicrobial carbon dots is expected to provide a powerful platform for the treatment of severe IK. In addition, the biomimetic design of the therapeutic platform to the natural corneal tissue in terms of high light transmittance, ECM composition, and mechanical properties still needs to be emphasized.
[0005] Traditional natural products have the advantages of strong biological activity, small antibacterial side effects, and low drug resistance. Curcumin is a multifunctional natural product with antioxidant and anti-inflammatory effects, but its poor water solubility greatly limits its bioavailability, bioactivity, and clinical application. Studies have shown that converting curcumin into zero-dimensional carbon can improve its antibacterial activity. Lin et al. synthesized quaternary ammonium carbon using curcumin and 2,3-epoxypropyltrimethylammonium chloride (GTA), improved the water solubility of carbon, and enhanced its antibacterial activity against Escherichia coli. However, GTA, as a common cationic surfactant, is usually not stable enough and has certain cytotoxicity. Chitosan, as a natural antibacterial product, is expected to solve the biocompatibility problem. However, whether the surface of CD made of natural products chitosan and curcumin can retain the active groups of curcumin and chitosan to enhance their antibacterial activity, especially whether a balance can be achieved between antibacterial and cytoprotective properties, remains an interesting question. In addition, natural products collagen and hyaluronic acid are the most important components of corneal tissue and are ideal raw materials for designing sutureless hydrogels for the preparation of corneal substitutes.
[0006] Application number: CN202110347174.5, invention name: A method for preparing a nano-modified titanium dioxide-chitosan-curcumin antibacterial complex, discloses a method for preparing a nano-modified titanium dioxide-chitosan-curcumin antibacterial complex, the method using glutaraldehyde as a cross-linking agent, and compounding the prepared glutaraldehyde-chitosan-curcumin complex gel with nano-silane modified titanium dioxide hydrogel to obtain an antibacterial complex. The present invention uses glutaraldehyde to react with amino groups in chitosan under certain conditions to form Schiff base, and converts chitosan linear polymer into a substance with a three-dimensional network structure, and the antibacterial activity of the formed Schiff base can also be enhanced; at the same time, the inorganic / organic antibacterial compound formed by using nano-modified titanium dioxide and curcumin not only makes up for the defects of curcumin as an antibacterial agent that is easily oxidized, has poor thermal stability and antibacterial durability when used alone, but also reduces the use cost of titanium dioxide, is safer and more environmentally friendly, and has improved antibacterial durability, and can be used as a multifunctional antibacterial pigment and an antibacterial and mildew-proof agent for coatings, leather, textiles, etc. The patent discloses an antibacterial and mildew-proof agent for coatings, leather, textiles, etc. using modified titanium dioxide as the main raw material. In situ hybridization of polymerized curcumin and arginine-derived carbon quantum dots for synergistic treatment of bacterial infections ACS Applied Materials & Interfaces (IF 8.3) Pub Date: 2023-05-28, DOI: 10.1021 / acsami.3c04316 Hong-Jyuan Jian, Anisha Anand, Jui-Yang Lai, Binesh Unnikrishnan, Huan-Tsung Chang, Scott G. Harroun, Chih-Ching Huang” The document discloses the preparation of arginine carbon dots, which are then compounded with curcumin to obtain hybrid nanoparticles, and are used in the form of eye drops for corneal bacterial infections. In situ light-triggered-imine cross-linked composite hydrogels for bone defect repair. Journal of Materials Chemistry B (IF 6.1) Pub Date: 2016-01-11, DOI: 10.1039 / c5tb02377g Jieyuan Zhang 1, Yunlong Yang, Yunfeng Chen, Xiaolin Liu, Shangchun Guo, Linyong Zhu, Yang Wang Affiliation” disclosed that HA-NB, as a photoresponsive component, participates in the cross-linking of the gel.
[0007] With the rapid spread of antibiotic resistance, the research on new antimicrobial drugs has become the focus of BK treatment. However, the cytotoxicity of antimicrobial drugs is a major problem in their clinical application. Although various efforts have been made to balance antimicrobial and biosafety, it remains challenging to reduce adverse reactions and promote corneal repair during the use of antibiotics. The main reason is that these materials destroy bacteria by directly upregulating reactive oxygen species (ROS) levels. However, they are generally toxic to both bacteria and cells. In addition, although corneal transplantation remains the ultimate means to restore the transparency of infected tissue, the shortage of corneal substitutes has severely limited the restoration of patients' vision. Especially in cases of severe keratitis, it is necessary not only to effectively resist the risk of secondary infection, but also to allow corneal substitutes to accurately fill corneal defects with minimal incision. Commonly used sutures may lead to serious potential complications, such as exacerbated infection and corneal neovascularization. Summary of the invention
[0008] The present invention provides an antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinking in-situ adhesion hydrogel, and also provides a preparation method and application of the hydrogel.
[0009] The present invention provides an antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinked in-situ adhesion hydrogel, which is prepared from bio-based carbon dots made of curcumin and carboxymethyl chitosan, mixed with double-bonded collagen and o-nitrobenzene functionalized hyaluronic acid, and chemically cross-linked under ultraviolet light to prepare a hydrogel.
[0010] Wherein, the weight ratio of curcumin, carboxymethyl chitosan, double-bonded collagen, and o-nitrobenzene functionalized hyaluronic acid is:
[0011] 1-3 parts of curcumin, 1-3 parts of carboxymethyl chitosan, 1-4 parts of double-bonded collagen, and 1-4 parts of o-nitrobenzene functionalized hyaluronic acid.
[0012] Preferably, the weight ratio of curcumin, carboxymethyl chitosan, double-bonded collagen, and o-nitrobenzene functionalized hyaluronic acid is:
[0013] 1 part of curcumin, 2 parts of carboxymethyl chitosan, 2 parts of double-bonded collagen, and 2 parts of o-nitrobenzene functionalized hyaluronic acid.
[0014] Wherein, the preparation method of the bio-based carbon dots is:
[0015] Weigh curcumin and carboxymethyl chitosan, place them in a beaker, and stir rapidly until they are evenly dispersed to form a dark yellow suspension; transfer them to a reactor containing a polytetrafluoroethylene liner, place them in an oven and react at 180°C for 8 hours; after the reaction is completed, cool them to room temperature; centrifuge the reaction solution at 8000r / min for 10 minutes to remove insoluble precipitates, and then place the supernatant in a 500 Dalton dialysis bag and dialyze for 3 days, changing the water every day; transfer the dialyzed liquid to a culture dish for freeze-drying, and the obtained black powder is the bio-based carbon dots CC-CDs.
[0016] Wherein, the preparation method of the double-bonded collagen is:
[0017] Use acetic acid solution to dissolve type I collagen at a concentration of 1% w / v; add methacrylic acid under magnetic stirring, and use NaOH to adjust the pH value to 7.4, and react for 4 hours; transfer the solution into a 8000-14000Da dialysis bag to remove unreacted small molecules, freeze-dry, and store in the dark to obtain the product.
[0018] Wherein, the preparation method of the o-nitrobenzene functionalized hyaluronic acid is:
[0019] Dissolve hyaluronic acid and amino-nitrobenzene in deionized water, and then add 1-hydroxybenzotriazole HOBt; adjust the pH of the mixed solution to 4.5, add 0.2g EDC hydrochloride, and react at room temperature for 48h; after the reaction is completed, transfer the solution to a 8000-14000Da dialysis bag to remove unreacted small molecules, then freeze-dry and store in the dark.
[0020] The present invention also provides a method for preparing the antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinked in-situ adhesion hydrogel, which comprises the following steps:
[0021] a. Prepare a 0.05% photoinitiator solution with 0.1M acetic acid;
[0022] b. using the initiator solution to dissolve the double-bonded collagen and o-nitrobenzene functionalized hyaluronic acid, maintaining the final concentration of the double-bonded collagen at 1%, and the final concentrations of the o-nitrobenzene functionalized hyaluronic acid at 0.5%, 1% and 2%, respectively;
[0023] c. The above solution was mixed with 100 ug / ml of bio-based carbon dots, the pH was adjusted to 7, and after incubation at 37°C for 30 min, ultraviolet light was irradiated for 60 s to achieve chemical cross-linking, and finally the antibacterial and anti-inflammatory bio-based carbon dots-photocross-linked in situ adhesion hydrogel CHB@CC was obtained.
[0024] The present invention also provides the use of the antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinked in-situ adhesion hydrogel described in the section in preparing an external medicine for treating infectious keratitis.
[0025] Wherein, the medicine is an external eye medicine.
[0026] The present invention also provides the use of the antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinking in-situ adhesion hydrogel in the preparation of a corneal substitute.
[0027] The present invention uses the natural herbal ingredient curcumin and chitosan rich in amino groups on the surface to successfully synthesize positively charged nanozyme activated carbon dots (CDs) by a simple hydrothermal method. Experiments have shown that, on the one hand, CDs can effectively destroy bacterial membranes and induce cytoplasmic DNA and RNA excretion due to their moderate positive charge, thereby killing bacteria. On the other hand, the retention of curcumin functional groups gives CDs powerful superoxide dismutase (SOD) and catalase (CAT) activities, thereby regulating ROS levels and achieving cell protection. In addition, the present invention also provides an injectable adhesive hydrogel with photoelasticity that can simulate extracellular matrix (ECM) components. A new type of nitrobenzene-grafted hyaluronic acid (HA-NB) is innovatively incorporated into methacrylate collagen. Under ultraviolet (UV) irradiation, methacrylate collagen is photopolymerized to form a hydrogel, thereby providing material stability and controlling the mechanical properties of the hydrogel. At the same time, NB-HA obtains in situ adhesion ability on the tissue surface through a light-triggered imine cross-linking (PIC) reaction. After adding curcumin-chitosan CDs (CC-CDs) to photostrictive Col-MA / HA-NB hydrogel (CHB@Gel), a composite hydrogel system (CHB@CC) was obtained, which can noninvasively fill corneal defects and effectively treat severe bacterial keratitis.
[0028] In addition, the in vitro antibacterial, cytoprotective, and macrophage polarization-regulating properties of the composite hydrogel were evaluated. After implantation of CHB@CC into corneal defects of bacterially infected rats, its ability to eliminate bacteria and inflammation and promote corneal repair was evaluated in vivo. Finally, the potential mechanism by which CHB@CC promotes the treatment of bacterial keratitis by balancing antibacterial and cytoprotective properties was also explored. This innovative all-natural hydrogel product is expected to become a clinical material for the treatment of infectious keratitis, especially bacterial keratitis.
[0029] The present invention prepares carbon dots by a one-pot method using carboxymethyl chitosan and curcumin with strong positive charge, with the purpose of integrating the antibacterial properties of carboxymethyl chitosan and the antioxidant properties of curcumin, and having certain enzyme-mimicking activity. The present invention also designs an adhesive hydrogel matrix for the problem of corneal transplantation faced by bacterial keratitis. Through the composite of carbon dots and gel, not only matrix filling can be achieved, but also effective antibacterial and antioxidant properties are achieved. The present invention uses HA-NB not only as an adhesive component, but also can undergo an imine cross-linking reaction with MA-Col. Ultraviolet light can not only excite HA-NB to expose aldehyde groups, but also achieve chemical cross-linking of MA-Col.
[0030] In severe viral keratitis, the infected corneal tissue needs to be removed. The hydrogel of the present invention can be filled in situ at the corneal defect and adhere to the corneal tissue in situ under ultraviolet light to form a tight connection.
[0031] The present invention provides a multifunctional bioinspired hydrogel matrix that not only has strong tissue adhesion but also has antibacterial, anti-inflammatory and antioxidant properties, which can be used to repair severely infected corneal wounds. As a corneal substitute, CHB@CC hydrogel has wound sealing, transparency and appropriate mechanical strength, which are key properties of sutureless hydrogels. In vitro and in vivo experiments have demonstrated that CHB@CC hydrogel not only has good biocompatibility, but also can reshape the microenvironment through antibacterial infection, antioxidant and anti-inflammatory effects, thereby accelerating wound healing. In summary, the application of this multifunctional hydrogel loaded with antibacterial and anti-inflammatory CDs provides a promising approach for the treatment of infectious keratitis. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 .(A) Schematic diagram of carbon dot synthesis; TEM (B), particle size distribution (C), UV-Vis absorption spectrum (D) and fluorescence excitation and emission spectrum (E) of carbon dots; (F) DPPH scavenging ability test of carbon dots; (G) hydroxyl radical scavenging ability test of carbon dots; (H) hydrogen peroxide scavenging ability test of carbon dots; (I) total antioxidant capacity test of carbon dots; SOD enzyme activity capacity test of carbon dots (J) and schematic diagram (K); CAT enzyme activity capacity test of carbon dots (L) and schematic diagram (M);
[0033] Figure 2 (A) Digital photos of the experiment of plating carbon dots with different concentrations; (B) SEM morphology of Escherichia coli and Staphylococcus aureus after treatment with 100ug / ml carbon dots; (C) Zeta potential test of bacteria and carbon dots; (D) Statistics of nucleic acid concentration in culture medium after treatment with 100ug / ml carbon dots; (E) Schematic diagram of carbon dots killing bacteria; Confocal image of co-culture of carbon dots and corneal epithelial cells (F) and interaction diagram (G);
[0034] Figure 3 Frequency scan (A), stress-strain curve (B), elongation at break (C), Young's modulus (D), optical photograph (E), transmittance (F), transmittance at 365nm (G), transmittance at 550nm of gel under different HA-NB concentrations; schematic diagram of lap shear adhesion experiment and adhesion strength statistics (I); schematic diagram of burst pressure test and numerical size statistics (J); swelling (K), degradation (L) and carbon dot release curve (M) of gel;
[0035] Figure 4:(A) Live-dead staining and cytoskeleton staining of Conrol, CHB-Gel, CC-CDs, and CHB@CC;(B) Cell proliferation data;(C) Reactive oxygen scavenging ability of different groups;(D) Immunofluorescence staining of TNF-α, IL-β, and IL-6. Fluorescence quantification of TNF-α(E), IL-β(E), and IL-6(E).(H) Flow cytometry data of Conrol, CHB-Gel, CC-CDs, and CHB@CC;
[0036] Figure 5 (A) Timeline of animal experiments on bacterial keratitis; (B) Optical photos and sodium fluorescein staining photos of the corneas of Conrol, CHB-Gel, CC-CDs, and CHB@CC groups at 1, 4, 7, and 28 days. Corneal epithelialization rate (C) and stromal thickness (D) at different time periods; (E) OCT images of the corneas of Conrol, CHB-Gel, CC-CDs, and CHB@CC groups at 1, 4, 7, and 28 days. DETAILED DESCRIPTION
[0037] Example 1 Preparation of the Antibacterial and Anti-inflammatory Bio-based Carbon Dot-Photocrosslinked In-situ Adhesion Hydrogel of the Present Invention
[0038] a. Preparation of Bio-based Carbon Dots
[0039] First, 30 mg of curcumin and 60 mg of carboxymethyl chitosan (CS) were weighed and placed in a beaker containing 40 ml of deionized water. They were stirred rapidly for 30 min until they were evenly dispersed and formed a dark yellow suspension. They were then transferred to a reactor lined with polytetrafluoroethylene and placed in an oven at 180 °C for 8 h.
[0040] After the reaction is completed, cool to room temperature. Centrifuge the reaction solution at 8000r / min for 10min to remove the insoluble precipitate, and then place the supernatant in a 500 Dalton dialysis bag for 3 days, changing the water 3 times a day. Transfer the dialyzed liquid to a culture dish for freeze drying, and the obtained black powder is CC-CDs.
[0041] b. Preparation of gel:
[0042] Preparation of double-bonded collagen (MA-Col): First, use 10 ml of 0.1 M acetic acid solution to dissolve type I collagen to a concentration of about 1% (w / v). Under magnetic stirring, add 0.5 ml of methacrylic acid, and use NaOH to adjust the pH value to about 7.4, and react for 4 hours. Transfer the solution to a 8000-14000Da dialysis bag to remove unreacted small molecules, then freeze-dry and store in the dark.
[0043] Preparation of o-nitrobenzene functionalized hyaluronic acid (HA-NB): 0.408g of hyaluronic acid and 0.224g of amino-o-nitrobenzene were dissolved in 50ml of deionized water, and 0.153g of HOBt was added. The pH of the mixed solution was then adjusted to 4.5, and 0.2g of EDC hydrochloride was added, and the mixture was reacted at room temperature for 48h. After the reaction was completed, the solution was transferred to a 8000-14000Da dialysis bag to remove unreacted small molecules, and then freeze-dried and stored in the dark.
[0044] Preparation of composite hydrogel (CHB@CC): First, 0.1M acetic acid was used to prepare a 0.05% photoinitiator solution, and then the initiator solution was used to dissolve MA-Col and HA-NB, keeping the final concentration of MA-Col at 1%, and the final concentration of HA-NB at 0.5%, 1% and 2%, respectively. The above solution was mixed with 100ug / ml CC-CDs, the pH was adjusted to 7, and after incubation at 37°C for 30min, UV light was irradiated for 60s to achieve chemical crosslinking, and finally CHB@CC composite hydrogel was obtained.
[0045] The beneficial effects of the present invention are demonstrated by pharmacodynamic tests as follows.
[0046] Experimental Example 1. Characterization of Antioxidant and Enzymatic Activities of CC-CDs
[0047] Curcumin (Cur) and carboxymethyl chitosan (CS) were reacted at 180 °C for 8 h to synthesize CC-CDs ( Figure 1 A). Figure 1 B depicts the TEM and HRTEM images of the obtained CC-CDs, indicating their good monodispersity and uniform size, with an average size of 2.9 ± 0.9 nm ( Figure 1 C). Figure 1 The inset in B shows that CC-CDs have a graphene-like layered structure with a lattice spacing value of 0.21 nm. Next, the optical properties of CC-CDs were further studied. The absorption spectrum of CC-CDs shows a wide absorption range from 350 to 800 nm, with a clear peak at 416 nm ( Figure 1 D). In addition, the prepared CC-CDs have strong fluorescence properties under the excitation wavelength of 366nm, and the optimal emission wavelength is 450nm ( Figure 1 E).
[0048] Curcumin is a natural polyphenol that has been widely studied as an antioxidant and anti-inflammatory molecule due to its excellent biocompatibility. However, curcumin has low bioavailability due to its strong hydrophobicity and rapid degradation and elimination. After converting curcumin into carbon dots, its water solubility is expected to be enhanced while retaining its antioxidant properties. Therefore, a series of experiments were designed to investigate the antioxidant properties of these carbon dots. It is well known that reactive oxygen and nitrogen species (RONS) mainly include nitric oxide (NO-), hydroxyl radicals (-OH), and hydrogen peroxide (H2O2). As a representative of nitrogen-centered free radicals, DPPH was first used to test the efficiency of CC-CDs in scavenging free radicals. Figure 1 As shown in Figure F, when DPPH comes into contact with CC-CDs, the characteristic absorption peak at 515nm is significantly reduced due to the scavenging effect of nitrogen-centered free radicals. It is worth noting that when the concentration is 100μg / ml, the scavenging efficiency is as high as 98%. At the same time, the ability of CC-CDs to scavenge -OH was studied using 3,3',5,5'-tetramethylbenzidine (TMB) as an indicator. 2+ / H2O2 Fenton reaction generates -OH in situ in aqueous solution. When hydroxyl radical (-OH) exists, it can react with TMB to generate oxidized TMB (oxTMB), which shows characteristic absorption peaks at 370 nm and 652 nm. Figure 1 As shown in Figure G, after adding CC-CDs, TMB+-OH complex did not show characteristic absorption peaks at 370 nm and 652 nm, indicating that CC-CDs have a strong scavenging ability for hydroxyl radicals. Hydrogen peroxide (H2O2) is also a major ROS in the body. Therefore, the ability of CC-CDs to scavenge H2O2 was also studied using a H2O2 detection kit. After 20 minutes of incubation, CC-CDs could scavenge 90% of H2O2 (1.0 mM), showing a high scavenging efficiency ( Figure 1 H). In addition, the total antioxidant capacity (TAC) of CC-CDs at different concentrations was evaluated, and the results are shown in Figure 1 I shows that the antioxidant activity of CC-CDs is concentration-dependent to some extent. Specifically, when the concentration is 100 μg / mL, the total antioxidant capacity of CC-CDs matches that of a standard solution containing 6 mM FeSO4, indicating that it has a strong and broad-spectrum ROS scavenging ability. It is particularly noteworthy that carbon dots generally exhibit more efficient catalytic activity due to their large specific surface area and abundant active groups. In order to further study the source of the antioxidant properties of carbon dots, the enzyme activity of CC-CDs was tested. As a key antioxidant enzyme in cells against ROS, SOD can catalyze -O 2- Dismutation to generate O2 and H2O2, thereby alleviating oxidative stress ( Figure 1K). Therefore, SOD mimetics are used as potential therapeutic agents to combat inflammatory diseases caused by oxidative stress. Figure 1 J showed that the catalytic performance increased significantly with the increase of CC-CDs concentration. When the concentration was 100 μg / ml, its SOD-like activity reached 80%. CAT enzyme can convert hydrogen peroxide into water and oxygen and is also an important antioxidant enzyme ( Figure 1 M). According to the determination of CAT enzyme activity kit, CC-CDs also have strong CAT activity, and its activity is related to concentration to a certain extent ( Figure 1 L).
[0049] In conclusion, curcumin and chitosan were combined by a hydrothermal method to synthesize CC-CDs that not only possessed potent antioxidant activity but also SOD-like and CAT-like activities, which would play a great role in inflammation-related environments.
[0050] Experimental Example 2. Evaluation of the antibacterial properties and bacteria-cell compatibility of carbon dots
[0051] Another role of synthesizing carbon dots using curcumin and chitosan as raw materials may be to endow them with excellent antibacterial properties. In order to investigate whether CC-CDs have universal antibacterial effects, Escherichia coli and Staphylococcus aureus were selected as models of Gram-negative and Gram-positive bacteria, and the antibacterial activity of carbon dots was evaluated by bacterial growth inhibition experiments.
[0052] like Figure 2 As shown in A, the growth of E. coli and S. aureus was affected by the dose of CC-CDs, and the bacterial viability gradually decreased as the concentration increased from 0 μg / mL to 10, 50, and 100 μg / mL. In addition, the morphological changes of E. coli and S. aureus after treatment with 100 μg / mL CC-CDs were observed using scanning electron microscopy. Figure 2 As shown in B, the bacteria in the untreated group maintained a smooth, undamaged membrane. In contrast, the cell walls and membranes of the bacteria treated with CC-CDs showed obvious wrinkles and damage. Zeta potential analysis further confirmed that both S. aureus and E. coli carried a negative charge (-15 ± 1.34 mV and -20 ± 1.4 mV), while the carbon dots carried a significant positive charge (-21 ± 3.4 mV). After 30 minutes of co-culture, the surface charge of the bacteria increased significantly, reaching (-4.8 ± 1.15 mV and -5.4 ± 1.28 mV) ( Figure 2 C). In addition, the bacterial nucleic acids (DNA and RNA) after incubation with CC-CDs were monitored. The results showed that after carbon dot treatment, both Escherichia coli and Staphylococcus aureus released a large amount of nucleic acids ( Figure 2D). The above results indicate that the positively charged CC-CDs have a high density of amine groups on their surface, which can selectively destroy bacterial cell walls through electrostatic interaction, leading to bacterial inactivation and the outflow of nucleic acids ( Figure 2 E).
[0053] At present, the design of antibacterial materials often only focuses on antibacterial properties, but in the body, bacteria often grow together with cells, and how to balance antibacterial and cell activity has received less attention. In the present invention, human corneal epithelial cells (HCECs) and Staphylococcus aureus were labeled with CM-FDA probe (green) and CM-Dil probe (red), respectively. Subsequently, CM-FDA-labeled HCECs and CM-Dil-labeled Staphylococcus aureus were co-cultured with 100μg / ml CC-CDs at the same time. After 24 hours, gentamicin (60μ / ml) was used to eliminate extracellular bacteria. Figure 2 F and Figure 2 As shown in G, compared with the blank group, most of the bacteria in the CC-CDs-treated group were in a dead state, and only very few cells were internalized and showed red fluorescence. It is worth noting that no obvious decrease in the number of cells was detected during this process, indicating that CC-CDs have good antibacterial and cell survival-promoting abilities.
[0054] Test Example 3. Characterization of burst pressure, adhesion and other physical properties of CHB@CC
[0055] It is noteworthy that the adhesive used in the present invention is based on an imine cross-linking (PIC) reaction triggered by strong light. Specifically, under light with a wavelength of 365 nanometers, the pro-nitrosobenzyl functional groups in the HA-NB precursor undergo photochemical conversion to pro-nitrosobenzaldehyde groups. These active aldehyde groups rapidly undergo imine cross-linking reactions with amines in the prepolymer solution or on the tissue surface, resulting in strong direct adhesion and endowing the potential for tissue sealing. At the same time, the effects of the adhesive component (i.e., HA-NB) on the mechanical properties and optical transparency of the hydrogel were first explored. Figure 3 As shown in Figure A, with increasing angular frequency, all samples exhibited gel-like behavior characterized by a storage modulus (G') exceeding the loss modulus (G"). With increasing HA-NB content, the G' and G" values of CHB hydrogels gradually increased, indicating that the addition of HA-NB helped to improve the mechanical toughness and viscoelastic behavior of the hydrogel structure. Tensile measurements showed that the ultimate stretch and elongation of CHB were closely related to the HA-NB content ( Figure 3B-3D). A reasonable explanation is that under UV irradiation, some of the generated benzaldehyde groups form dynamic covalent bonds with the amino groups in collagen, thereby enhancing the mechanical stability (from 38±3Kpa to 76±4Kpa) and resilience (from 20±0.6% to 62±5%) of the hydrogel network. In addition, although the addition of HA-NB gave the CHB hydrogel a slight yellow color, according to the transmittance analysis, it had little effect on its transmittance in the visible spectrum. In contrast, a more obvious effect was observed in the ultraviolet (UV) range ( Figure 3 E-3H). When the concentration of HA-NB was 1%, the transmittance of CHB hydrogel at 550 nm wavelength was 91 ± 2%, while the transmittance at 365 nm wavelength was only 42 ± 2.6 nm. The above experiments show that the addition of HA-NB can enhance the UV resistance of the hydrogel matrix without affecting its overall optical clarity in the visible light region, which is particularly beneficial for the development of corneal substitutes.
[0056] Importantly, hydrogels used for sutureless repair of severe fistulas need to have sufficient adhesion to adjacent tissues to withstand high intraocular pressure and avoid detachment from the eyeball. Here, key properties for effective bioadhesion, including shear adhesion strength and burst pressure, were investigated. The adhesion properties of the hydrogels were first tested using the lap shear method ( Figure 3 I). Figure 3 The inset in Figure I shows that the hydrogel formed in situ on pig skin tissue can withstand water flow impact, bending and twisting. Figure 3 As can be seen from Figure 1, the shear adhesion strength of pure MA-Col@CC hydrogel is relatively low (18±1.73 kPa). With the increase of HA-NB concentration and the introduction of aldehyde groups, the shear adhesion strength of the hydrogel is greatly improved. CHB@CC-2% has the best shear adhesion strength (53.2±1.4 kPa). Figure 3 J, a simple device was constructed to test the burst pressure. Figure 3 It can be clearly observed in Figure 5 that the burst pressure of the hydrogel gradually increased with the increase of HA-NB concentration. When the HA-NB concentration reached 2%, the adhesion strength reached 236±30mmHg. This quantitative data emphasizes the robust adhesion properties of the hydrogel at this concentration, indicating its potential for effective tissue fixation in clinical applications. Interestingly, there was no significant difference in the burst pressure between the CHB@CC-1% group and the CHB@CC-2% group, both of which were sufficient for sealing corneal defects. These results indicate that the addition of HA-NB can improve the mechanics, adhesion strength, and burst pressure of the hydrogel. Considering the effects on mechanics and transmittance, the hydrogel containing 1% HA-NB was selected for the next experiment.
[0057] The expansion rate is a key indicator for judging the quality of tissue adhesives. A lower expansion rate is beneficial for tissue adhesion. In terms of keratoplasty applications, adhesives with low expansion rates help maintain perfect alignment between the graft and the recipient cornea, thereby reducing postoperative corneal astigmatism. The results showed that the CHB hydrogel had a low expansion rate (about 28%). After the addition of CC-CDs, the expansion rate was even lower (about 23%), which may be because the amino groups on the surface of CC-CDs formed new bonds with the aldehyde groups on the polymer chain, increasing the density of the hydrogel network ( Figure 3 K). In addition, as an excellent corneal substitute, its excellent degradation resistance can match the corneal regeneration rate and prevent the cornea from falling off prematurely. Here, the present invention tests the enzymatic degradation of CHB and CHB@CC hydrogels under the action of collagenase. Figure 3 As shown in Figure 1, the introduction of CC-CDs improved the resistance of the hydrogel to enzymatic degradation, which was similar to the change trend of the swelling rate. After 24 h, the CHB@CC hydrogel was only degraded by 40%, while the CHB hydrogel was degraded by 60%. The increase in the degree of cross-linking can easily explain this trend. As a functional component, the slow release of CC-CDs is very important to achieve the repair of keratitis damage. Figure 3 The release curves in M show that CHB@CC hydrogel is able to achieve a slow release of CC-CDs, with only 40% released after 20 h.
[0058] In summary, the designed hydrogel not only has excellent mechanical, optical and adhesive properties, but also has low swelling and degradation resistance, and can achieve slow release of carbon dots when loaded. The integration of these properties is expected to develop a class of corneal substitutes for repairing severe keratitis with universal applicability.
[0059] Experimental Example 4. In vitro cytocompatibility, antioxidant and anti-inflammatory properties of CHB@CC
[0060] Good biocompatibility is the basis for the in vivo application of CHB@CC hydrogel. In order to evaluate the biocompatibility of CHB@CC hydrogel, live / dead staining and MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) detection were used. Figure 4 As shown in A, strong green fluorescence and weak red fluorescence were observed in human corneal epithelial cells (HCECs), which confirmed that the prepared hydrogel had good biocompatibility. Figure 4The quantitative data in B showed that the survival rate of cultured cells in the hydrogel group was greater than 95% compared with the control group, with no obvious cytotoxicity. It is worth noting that the survival rate of the group with CC added alone was 80±5%, indicating that the one-time addition of carbon dots may be toxic. Cytoskeleton staining showed that the morphology of CHB@CC hydrogel was more dispersed, indicating that it can maintain the cell structure and morphology and promote the migration and proliferation of corneal epithelial cells. Then, 2′,7′-dichlorofluorescein diacetate (DCFH-DA) was used as a fluorescent probe, and H2O2-induced intracellular oxidative stress in HCECs was used to detect the ROS scavenging effect of different coatings. Figure 4 As shown in C, the control group and CHB-Gel group showed clear green fluorescence, indicating that HCECs produced ROS in the cells under the stimulation of H2O2. Compared with the CC-CDs group, the CHB@CC group had almost no green fluorescence, indicating that the CDs slowly released in the hydrogel effectively alleviated the oxidative stress in the cells.
[0061] After bacterial infection, the immune system will produce inflammatory responses and oxidative stress. In order to simulate the anti-inflammatory and antioxidant effects of hydrogels in vitro, RAW 264.7 cells were selected as a cell model, and lipopolysaccharide (LPS) was stimulated to produce an inflammatory response. The expression of multiple inflammatory factors in the cells, including interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α), was observed after immunofluorescence staining. The results showed that the cells in the CHB hydrogel group showed obvious fluorescence intensity, indicating that the inflammatory factors IL-1β, IL-6, and TNF-α were expressed in large quantities. However, in the CC group and the CHB@CC group, the green fluorescence was significantly reduced, indicating that the expression of IL-1β, IL-6, and TNF-α was highly reduced, which demonstrated the anti-inflammatory effect by eliminating oxidative stress ( Figure 4 D). In addition, the fluorescence quantitative data showed that the expression level of the CHB@CC group was significantly lower than that of the CC group, indicating that the sustained-release anti-inflammatory effect of the gel-loaded CD was the best ( Figure 4 E-4G). In addition, Figure 4 Flow cytometry analysis in H showed that CHB@CC hydrogels could significantly upregulate the expression of CD206 and downregulate the expression of CD86. This suggests that CD-loaded hydrogels can promote the repolarization of M1 macrophages to the M2 phenotype, thereby alleviating inflammation.
[0062] Test Example 5. Evaluation of corneal wound healing in vivo CHB@CC:
[0063] The primary goal of designing CHB@CC hydrogel is to use it as a corneal substitute to accelerate wound healing in patients with severe IK. To further understand the potential of CHB@CC hydrogel in promoting corneal wound healing, the present invention conducted an in vivo study using a New Zealand rabbit lamellar keratectomy corneal wound infection model.
[0064] Figure 5 A shows the detailed process of lamellar keratectomy, bacterial infection, and treatment. Specifically, a partial keratectomy corneal defect (3.5 mm in diameter and 250 μm in depth) was first made on the rabbit cornea, and then the S. aureus bacterial suspension was injected into the corneal defect, followed by treatment with CHB-gel, CC-CDs, and CHB@CC hydrogel. All procedures were approved by the Animal Research Committee.
[0065] Rabbits were examined routinely with slit lamp light and fluorescein staining at 1, 4, 7, 14, and 28 days intervals. Figure 5 The slit lamp images on day 1 in B show that there is almost no bacterial infection in the CC@CC and CHB@CC groups compared with the control group, verifying the antibacterial effect of carbon dots in vivo. It is obvious that the CHB-Gel and CHB@CC groups can stably fill and fit the contour of the corneal defect, demonstrating their strong tissue adhesion properties. In addition, Figure 5 As shown in Figures C and 5D, the wounds treated with CHB@CC hydrogels were completely re-epithelialized within 4 days, while the epithelial defects in the control group persisted even after 28 days due to severe IK, indicating that CHB@CC hydrogels can accelerate wound re-epithelialization. Although the CHB-gel group achieved the filling of the corneal defect, the epithelialization process may be affected due to residual bacteria. The CC-CDs group alone also inhibited the epithelialization process because the rapid clearance mechanism of the ocular surface affected the antibacterial effect. AS-OCT images collected on day 28 showed that all hydrogel-treated groups had dense stromal tissue and newly formed corneal epithelium compared with the control group ( Figure 5 E). After 28 days of treatment, the corneas treated with CHB@CC showed similar optical reflectivity and structural characteristics to the native cornea, while the corneas of the other groups showed obvious scarring in the pupil area. In conclusion, CHB@CC hydrogels exhibited excellent antibacterial efficacy, strong tissue adhesion, and outstanding corneal wound healing ability in vivo. CHB@CC hydrogels can promote rapid corneal re-epithelialization and restore corneal structure, and therefore are expected to become a therapeutic approach for severe infectious keratitis.
Claims
1. An antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinked in-situ adhesion hydrogel, characterized by: It is prepared from bio-based carbon dots made of curcumin and carboxymethyl chitosan, mixed with double-bonded collagen and o-nitrobenzene functionalized hyaluronic acid, and chemically cross-linked under ultraviolet light to prepare a hydrogel.
2. The antibacterial and anti-inflammatory bio-based carbon dots-photocrosslinked in-situ adhesion hydrogel according to claim 1, characterized in that: The weight ratio of the curcumin, carboxymethyl chitosan, double-bonded collagen, and o-nitrobenzene functionalized hyaluronic acid is: 1-3 parts of curcumin, 1-3 parts of carboxymethyl chitosan, 1-4 parts of double-bonded collagen, and 1-4 parts of o-nitrobenzene functionalized hyaluronic acid.
3. The antibacterial and anti-inflammatory bio-based carbon dots-photocrosslinked in-situ adhesion hydrogel according to claim 1, characterized in that: The weight ratio of the curcumin, carboxymethyl chitosan, double-bonded collagen, and o-nitrobenzene functionalized hyaluronic acid is: 1 part of curcumin, 2 parts of carboxymethyl chitosan, 2 parts of double-bonded collagen, and 2 parts of o-nitrobenzene functionalized hyaluronic acid.
4. The antibacterial and anti-inflammatory bio-based carbon dots-photocrosslinked in-situ adhesion hydrogel according to any one of claims 1 to 3, characterized in that: The preparation method of the bio-based carbon dots is: Weigh curcumin and carboxymethyl chitosan, place them in a beaker, and stir rapidly until they are evenly dispersed to form a dark yellow suspension; transfer them to a reactor containing a polytetrafluoroethylene liner, place them in an oven and react at 180°C for 8 hours; after the reaction is completed, cool them to room temperature; centrifuge the reaction solution at 8000r / min for 10 minutes to remove insoluble precipitates, and then place the supernatant in a 500 Dalton dialysis bag and dialyze for 3 days, changing the water every day; transfer the dialyzed liquid to a culture dish for freeze-drying, and the obtained black powder is the bio-based carbon dots CC-CDs.
5. The antibacterial and anti-inflammatory bio-based carbon dots-photocrosslinked in-situ adhesion hydrogel according to any one of claims 1 to 3, characterized in that: The preparation method of the double-bonded collagen is as follows: Use acetic acid solution to dissolve type I collagen at a concentration of 1% w / v; add methacrylic acid under magnetic stirring, and use NaOH to adjust the pH value to 7.4, and react for 4 hours; transfer the solution into a 8000-14000Da dialysis bag to remove unreacted small molecules, freeze-dry, and store in the dark to obtain the product.
6. The antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinked in-situ adhesion hydrogel according to any one of claims 1 to 3, characterized in that: The preparation method of the o-nitrobenzene functionalized hyaluronic acid is: Dissolve hyaluronic acid and amino-nitrobenzene in deionized water, and then add 1-hydroxybenzotriazole HOBt; adjust the pH of the mixed solution to 4.5, add 0.2g EDC hydrochloride, and react at room temperature for 48h; after the reaction is completed, transfer the solution to a 8000-14000Da dialysis bag to remove unreacted small molecules, then freeze-dry and store in the dark.
7. The method for preparing the antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinked in-situ adhesion hydrogel according to any one of claims 1 to 6, characterized in that: It includes the following steps: a. Prepare a 0.05% photoinitiator solution with 0.1M acetic acid; b. using the initiator solution to dissolve the double-bonded collagen and o-nitrobenzene functionalized hyaluronic acid, maintaining the final concentration of the double-bonded collagen at 1%, and the final concentrations of the o-nitrobenzene functionalized hyaluronic acid at 0.5%, 1% and 2%, respectively; c. The above solution was mixed with 100 ug / ml of bio-based carbon dots, the pH was adjusted to 7, and after incubation at 37°C for 30 min, ultraviolet light was irradiated for 60 s to achieve chemical cross-linking, and finally the antibacterial and anti-inflammatory bio-based carbon dots-photocross-linked in situ adhesion hydrogel CHB@CC was obtained.
8. Use of the antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinked in situ adhesion hydrogel according to any one of claims 1 to 6 in the preparation of an external medicine for treating infectious keratitis.
9. The use according to claim 8, characterized in that: The medicine is an external medicine for eyes.
10. Use of the antibacterial and anti-inflammatory bio-based carbon dot-photocrosslinked in situ adhesion hydrogel according to any one of claims 1 to 6 in the preparation of a corneal substitute.
Citation Information
Patent Citations
Preparation method of nano modified titanium dioxide-chitosan-curcumin antibacterial compound
CN113057177A
Preparation method of tissue adhesive for repairing meniscus tearing
CN115591007A
Curcumin-carbon dot compound as well as preparation method and application thereof
CN117925222A
COLLAGEN-BASED HYDROGELS LOADED WITH ZnO QDs / pDNA COMPLEXES AS CORNEAL SUBSTITUES
US20120009223A1
Method for preparing non-free radical photochemical crosslinking hydrogel material, and product and application thereof
WO2016082725A1
Cited By
Fluorescent carbon dot-nucleic acid adhesive based on liquid-liquid phase separation as well as preparation method and application of fluorescent carbon dot-nucleic acid adhesive
CN121003724A